The role of biotransformation and oxidative stress in 3, 5-dichloroaniline (3, 5-DCA) induced nephrotoxicity in isolated renal cortical cells from male Fischer 344 rats. (3rd February 2016) - Racine, Christopher R.; Ferguson, Travis; Preston, Debbie; Ward, Dakota; Ball, John; Anestis, Dianne; Valentovic, Monica; Rankin, Gary O.
Abstract: Among the mono- and dichloroanilines, 3, 5-dichloroaniline (3, 5-DCA) is the most potent nephrotoxicant in vivo and in vitro. However, the role of renal biotransformation in 3, 5-DCA induced nephrotoxicity is unknown. The current study was designed to determine the in vitro nephrotoxic potential of 3, 5-DCA in isolated renal cortical cells (IRCC) obtained from male Fischer 344 rats, and the role of renal bioactivation and oxidative stress in 3, 5-DCA nephrotoxicity. IRCC (∼4 million cells/ml) from male rats were exposed to 3, 5-DCA (0–1.0 mM) for up to 120 min. In IRCC, 3, 5-DCA was cytotoxic at 1.0 mM by 60 min as evidenced by the increased release of lactate dehydrogenase (LDH), but 120 min was required for 3, 5-DCA 0.5 mM to increase LDH release. In subsequent studies, IRCC were exposed to a pretreatment (antioxidant or enzyme inhibitor) prior to exposure to 3, 5-DCA (1.0 mM) for 90 min. Cytotoxicity induced by 3, 5-DCA was attenuated by pretreatment with inhibitors of flavin-containing monooxygenase (FMO; methimazole, N -octylamine), cytochrome P450 (CYP; piperonyl butoxide, metyrapone), or peroxidase (indomethacin, mercaptosuccinate) enzymes. Use of more selective CYP inhibitors suggested that the CYP 2C family contributed to 3, 5-DCA bioactivation. Antioxidants (glutathione, N -acetyl-l -cysteine, α-tocopherol, ascorbate, pyruvate) also attenuated 3, 5-DCA nephrotoxicity, but oxidized glutathione levels and the oxidized/reduced glutathione ratios were not increased. These results indicate that 3, 5-DCA may be activated via several renal enzyme systems to toxic metabolites, and that free radicals, but not oxidative stress, contribute to 3, 5-DCA induced nephrotoxicity in vitro.